A Case of Resolving Pontine Hemorrhage - Gurukanth Rao; S. Vaibhav; Jayaprakash Belle (Wolters Kluwer Medknow Publications, 2022)
Generally, Pontine hemorrhages though rare have poor prognosis with 48.1% all-cause mortality noted. A grim statistic which becomes worse if the patient presents to the hospital with depressed sensorium. Level of consciousness and hemorrhage size constitute two of the most important prognostication factors for patients with pontine hemorrhage. Here we present a case of a young lady who presented with poor sensorium and a large pontine hemorrhage who went on to return to good recovery status, modified Rankin Score 2 with conservative intervention.